2009
DOI: 10.1111/j.1532-950x.2009.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Bone Lengthening in Dogs by Means of Backscattered Scanning Electron Microscopy

Abstract: BS-SEM is an effective technique for studying progression of bone healing during DO. The presence of chondroid tissue during DO explains why callus mineralization occurs more rapidly during distraction than during static stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…It has a faster calcification and contains types I and II collagen fibers [65,66]. Woven, lamellar, and osteonal bone are the calcified tissues that replace chondroid bone in our histological and BS-SEM findings, in a similar manner to the one seen in other endomembranous ossification-based processes, such as mandibular symphysis closure [62], skull suture growth and closure [67,68,69], tooth eruption [70,71], fracture repair [59,60,61,62,63,64,65,66,67], and, more recently, the osseointegration of non-metallic biomaterials [14,35].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It has a faster calcification and contains types I and II collagen fibers [65,66]. Woven, lamellar, and osteonal bone are the calcified tissues that replace chondroid bone in our histological and BS-SEM findings, in a similar manner to the one seen in other endomembranous ossification-based processes, such as mandibular symphysis closure [62], skull suture growth and closure [67,68,69], tooth eruption [70,71], fracture repair [59,60,61,62,63,64,65,66,67], and, more recently, the osseointegration of non-metallic biomaterials [14,35].…”
Section: Discussionsupporting
confidence: 74%
“…The tissues of the first trabeculae that surround the granules as well as the ones formed as a response to the periosteal injury are mainly constituted by chondroid bone [64]. It has a faster calcification and contains types I and II collagen fibers [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chondroid tissue, also described by Bailleul et al [ 25 ] as “chondroid bone”, in the initial trabeculae surrounding the biomaterial ( Fig 5 ), as identified by back scattered SEM [ 26 ], cannot necessarily be interpreted as endochondral ossification. In fact, it has been demonstrated that chondroid tissue is an essential part of the human skull membranous ossification [ 27 , 28 ] and other repair processes [ 29 , 30 ], even if it can be present also in endochondral ossification. Moreover Bailleul et al [ 25 ] described very thoroughly the evolution, morphological characteristics, and participation of chondroid tissue in endomembranous ossification in different species, as they have been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in distraction gaps the tissue between the ends of the mineralised bone is first subject to bleeding, coagulation, granulation tissue and fibrosis (Kokich, 1976;Shapiro, 2008), bone directly develops at the suture edges in craniosynostosis. In addition, in contrast to the distraction gap (Yasui et al, 1997;Jazrawi et al, 1998;Sato et al, 1998;Ploder et al, 2002;Lafuente et al, 2009;Forriol et al, 2010), our analyses of sutural sites showed no verification of enchondral and transchondroid types of osteogenesis.…”
Section: J Regelsberger Et Almentioning
confidence: 41%